Human progress and development - Bonefeld, Werner, (Universidad Nacional de Quilmes, 2003)
If development as human progress takes itself seriously, it has to reveal the deceitful publicity of development as capitalist freedom. Development as capitalist freedom is currently discussed under the heading globalisation. The pros and cons of the globalisation debate are well established; has the economy escaped the national state irretrievably or does the national state retain regulative power over the economy. The question, then, is that of relative autonomy; has globalisation established the autonomy of the economy over the state or does the state at least potentially retain autonomy over the economy, should the balance of class forces change in favour of labour. This article approaches globalisation from quite different perspectives. It explores the human content of globalisation and analyses the political constitution of economic categories. The conclusion discusses the issue of human progress as human self-emancipation and offers some practical suggestions, both on the danger of nationalist conceptions of anti-globalisation and on anti-globalisation as a project of human freedom. The argument urges that in the struggle for the equality of individual human needs, it is precisely necessary to avoid ever again to counterpose "society" as an abstraction to the individual (Marx).